Water is a safe and effective alternative to sterile normal saline for wound irrigation prior to suturing: a prospective, double-blind, randomised, controlled clinical trial. Issue 1 (16th January 2013) - Weiss, Eric Alan; Oldham, George; Lin, Michelle; Foster, Tammy; Quinn, James Victor
Abstract : Objective: To determine if there is a significant difference in the infection rates of wounds irrigated with sterile normal saline (SS) versus tap water (TW), before primary wound closure. Design: Single centre, prospective, randomised, double-blind controlled trial. Wound irrigation solution type was computer randomised and allocation was done on a sequential basis. Setting: Stanford University Medical Center Department of Emergency Medicine. Participants: Patients older than 1 year of age, who presented to the emergency department with a soft tissue laceration requiring repair, were entered into the study under informed consent. Exclusion criteria included any underlying immunocompromising illness, current use of antibiotics, puncture or bite wounds, underlying tendon or bone involvement, or wounds more than 9 h old. Interventions: Non-caregivers used a computer generated randomisation code to prepare irrigation basins prior to treatment. Patients had their wounds irrigated either with TW or SS prior to closure, controlling for the volume and irrigation method used. The patient, the treating physician and the physician checking the wound for infection were all blind regarding solution type. Structured follow-up was completed at 48 h and 30 days to determine the presence of infection. Main outcome measures: The primary outcome measured was the difference in wound infection rates between the two randomised groups. Results: During the 18-month study period, 663 consecutive patients were enrolled. After enrolment, 32 patients were later excluded; 29 patients because they were concurrently on antibiotics; two patients secondary to steroid use and one because of tendon involvement. Of the 631 remaining patients, 318 were randomised into the TW group and 313 into the SS group. Six patients were lost to follow-up (5 SS, 1 TW). A total of 625 patients were included in the statistical analysis. There were no differences in the demographic and clinical characteristics of the two groups. There were 20 infections 6.4% (95% CI 9.1% to 3.7%) in the SS group compared with 11 infections 3.5% (95% CI 5.5% to 1.5%) in the TW group, a difference of 2.9% (95% CI −0.4% to 5.7%). Conclusions: There is no difference in the infection rate of wounds irrigated with either TW or SS solution, with a clinical trend towards fewer wound infections in the TW group, making it a safe and cost-effective alternative to SS for wound irrigation.